Growth Hormone Deficiency Is Frequent After Recent Stroke - Lillicrap, Thomas; Garcia-Esperon, Carlos; Walker, Frederick Rohan; Ong, Lin Kooi; Nilsson, Michael; Spratt, Neil; Levi, Christopher R.; Parsons, Mark; Isgaard, Jörgen; Bivard, Andrew (Frontiers in Neurology, 2018)
Introduction: The incidence of pituitary dysfunction after ischemic stroke is unknown, however given the increasing attention to pituitary dysfunction after neurological injuries such as traumatic brain injury, this may represent a novel area of research in stroke. In the present study we aimed to assess the rate of growth hormone deficiency after stroke. Methods: We perform an arginine and human growth hormone releasing hormone challenge on ischemic stroke patients within a week of symptom onset. Results: Over the study period, 13 patients were successfully tested within a week of stroke (baseline NIHSS 10, range 7-16). Overall, 9(69%) patients had a poor response, with 7(54%) of these patients meeting the criteria for had human growth hormone deficiency. Other measures of pituitary function were within normal ranges. Conclusion: After major ischemic stroke, low GH levels are common.